Antioxidant Potential of Madura Knife Scallop (Solen sp) Extract as a Prevention of Oxidative Stress - Anggarani, Mirwa Adiprahara; Irawan, Roy Januardi (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
Reactive Oxygen Species (ROS) are produced by humans as a result of cellular metabolism and environmental factors such as pollutants or cigarette smoke. ROS is a very reactive molecule and has the ability to damage cell structure. Oxidative stress is a condition between oxidants and antioxidants that is not balance, pathophysiologically, oxidative stress can trigger the risk of various diseases including hypertension, atherosclerosis, diabetes, heart failure, stroke and other chronic diseases. Oxidative stress can be overcome by intake of antioxidants. The purpose of this study was to determine the antioxidant activity contained in the meat and shells of a knife scallop (Solen sp.) that lives in Bangkalan waters, Madura. The method used in this study is an analysis of antioxidant activity with the DPPH method. Knife scallop has antioxidant activity which is evident from the IC50 values obtained. IC50 values of the shell and meat extract with ethanol solvent were 489.56 ppm and 748.49 ppm. IC50 values of the shell and meat extract with ethyl acetate solvent were 916.43 ppm and 2045.93 ppm. While the IC50 value of the shell and meat extract with chloroform solvent was 119.37 ppm and 1692.80 ppm. Based on IC50 data of knife scallop shell and meat extracts on the 3 types of solvents, it can be concluded that knife scallop’s shell and meat extract with ethanol solvent has the greatest antioxidant activity compared to ethyl acetate and chloroform solvents.